IncP-1 plasmids in antibiotic resistant Enterobacteriaceae - Chidiamassamba, Sekerani Benedito (2022)
Antibiotic resistance is increasing worldwide closely linked with antibiotic misuse and overuse. Antibiotic gene resistance is commonly disseminated through MGEs (mobile genetic elements), especially plasmids. IncP-1 plasmids are BHR presumably found in several bacterial families and have been associated with antibiotic resistance and tolerance to metals. The identification of plasmid groups has been frequently done using the PBRT (PCR-based replicon typing) approach which assigns plasmids to Inc groups, including the IncP-1 plasmid group. The efforts to further characterize these structures, especially when associated with antibiotic resistant bacteria, has been lacking, and consequently, information is scarce and dispersed. Therefore, a systematic analysis was carried out to understand the occurrence, distribution, and genetic traits of IncP-1 plasmids associated with antibiotic resistant bacteria. To do so, a bibliographic search strategy was followed, where the Scopus platform was used to look for studies that used the PBRT method developed by Carattoli et al. (2005) for plasmid identification and that actually detected IncP-1 plasmids structures. Article collection for a period of 5 years resulted in 96 eligible articles, which were used to retrieve relevant information about IncP-1 plasmids occurrence and features. The articles combined reported the identification of 629 IncP-1 replicons. Altogether, the bacterial hosts of IncP-1 plasmids were found in 32 countries and were collected from a variety of environmental sources. Bacterial hosts belonged to 28 species distributed in 10 genera, of Enterobacteriaceae and Pseudomonadaceae families and were resistant to 10 different antibiotic classes, harboring 32 different resistance genes. IncP-1 plasmid-positive bacteria usually harbored at least 2 different Inc groups. Of all the IncP-1 plasmids identified, 229 (~36%) were further described, their sizes ranging from 35 to 320 kb and have been associated with medically important resistance genes and additional genetic elements that could potentiate gene dissemination. Furthermore, we studied the molecular diversity of previously reported IncP-1 plasmids occurring in 9 Escherichia coli isolates from an UWTP in Portugal. This was accomplished via PCR amplification of the 281 bp trfA gene fragment sequences and transfer to new well-known bacterial hosts for further characterizations. Amplicon sequencing showed 100% identity in all trfA fragments suggesting genetic structure conservation association to similar bacteria and environments. Similarity searching of the trfA fragment sequence was used to select closely related fully sequenced IncP-1β1 plasmids for comparisons. As a result, 63 closely related replicons were selected for comparative analysis and found to be usually large genetic structures, isolated mainly from wastewater and soil, harboring genetic determinants associated with resistance to aminoglycosides, sulphonamides, and β-lactams, and with tolerance to Hg. Attempts to transfer the 9 IncP-1 plasmids to a recipient strain were unsuccessful probably due to the chosen selective markers. The high prevalence of mer operon genes in these IncP-1β1 plasmids, suggesting mercury tolerance, could be used in a future work as a selective marker to transfer these 9 IncP-1 plasmids another bacterial host allowing for proper genomic characterization of these promiscuous structures.